Creating a bubble…and an understanding of scientific practices. (2nd October 2018) - Ashmann, Scott; Gichobi, Mary
Abstract: The use of creativity in science practices is many times lost on secondary students. Creativity is seen as something central to the arts and humanities, but tangential at best in the sciences. However, an examination of many great scientific discoveries and the work of everyday contemporary scientists shows the depth and breadth of the use of creativity in the scientific process. Creating a Bubble is an activity that can be used in a secondary classroom to help students understand not only the importance of creativity in science practices, but also the role of communication, the open-endedness of scientific endeavors, and the use of others' ideas. Students are given a straw, Styrofoam cup, and dish soap and asked to create a big bubble consistently. At first, the techniques that are used produce many small bubbles. Eventually, someone asks how big a big bubble is. Armed with the knowledge that a big bubble is at least 33 cm (13-inches) in diameter, students become very creative in the techniques they try. They learn from each other and eventually are successful in their quest. Frustration and persistence are also key ingredients along their journey.